Istibdal Wakaf Saham pada Tabung Wakaf Indoesia: Legalitas dan Dampaknya - Muhammad Aiz (JURNAL INDO-ISLAMIKA, 2016)
The grand conclusion of this dissertation is the more contextual the qiyiis the more beneficial it is for the people. In line with that, there is a shift paradigm from "habs al-esl" (maintaining the immortality of the wakaf object )  to a pradigm of "tasbil  al- thamsreli” (preservance  and development of the benefit of waqf) which opens the path selectively to  the istibdal of waqf objects to be relevant with the share waqf management at present time.The finding is that in practice of istibdal in Tabung Wakaf Indonesia (TWI), the tendency of to use of the Hanafi understanding in the context of the continuing exclusion of qadi (judge/government) for having their associated sigh at of wakif istibdal in relation with process can be done by Nazhir. In addition, in the context of replacing old waqf object (shares) with a new waqf objects that are not similar (parking lot behind the financing and other waqf stock name) is based on the principles of the Hanbali Islamic school. This type of research is qualitative through field study and library research. In conducting this research, the author analyzes the sociolegal approach (socio legal research).